A Novel Medical Student Assistant Accommodation Model for a Medical Student With a Disability During a Required Clinical Clerkship. Issue 3 (19th December 2019) - Jauregui, Joshua; Strote, Jared; Addison, Conrad; Robins, Lynne; Shandro, Jamie
ABSTRACT: Background: As efforts continue to diversify the physician workforce so that it better matches the patient population, the number of medical students with disabilities will increase. U.S. medical schools and emergency medicine (EM) clerkships should be prepared to provide full and meaningful access to learners with disabilities. Methods: We created a novel means of providing access to a senior medical student with a mobility disability (secondary to a cervical spinal cord injury) to participate in a fourth‐year EM clerkship. We hired four second‐year medical students as intermediaries to perform senior medical student–directed physical examination maneuvers, during his 15 required 8‐hour emergency department shifts. The senior medical student dictated his documentation using Dragon Natural Speaking (Nuance Communications, 2015) voice recognition software. Results: The senior medical student successfully completed the required clinical clerkship and earned a honors grade for his work. Both the senior medical student and the second‐year medical student intermediaries gave positive feedback about the experience. Conclusions: Given the significant prevalence of disability among medical students in U.S. medical schools, medical educators should provide greater access to students with disabilities and opportunities for advanced education for all learners by creating innovative clinical curriculum. The authors recommend the student intermediary model for senior medical students with physical disabilities in required clinical clerkships.